The OPIT system II: job control and scheduling for large applications programs - Brailsford, David F.; Prentice, John A. (Elsevier, 1973)
A strategy is described for a controlling algorithm (‘the job’) to schedule and supply many data sets (‘problems’) to a large, long-running applications program. The algorithm also controls very closely the run time environment of each problem and provides protection against breakdown of the computer or its operating system. The principles described are applicable on any computer with a sufficiently flexible operating system. The particular example used here is the running of the OPIT Program (see paper I page 123) on an ICL 1900 Computer with the GEORGE 3 operating system.